Budaya dan Bahasa : Refleksi Dinamis Identitas Masyarakat - Bella Tiara Putri; Citra Sukma Ayu; Mita Atiiqah Br Ginting; Siti Saidah; Sahkholid Nasution (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study explores the relationship between language, culture, and society, all three of which are interdependent and inseparable. Language and culture are integral components that shape the identity of a society, and language functions as a cultural mirror and social glue. The method used is a qualitative approach based on literature which aims to examine the importance of language and culture in forming community identity. The results of the study are then narrated in descriptive form. This research aims to study and understand the concept of culture and language about how cultural changes influence the evolution of language and shape the identity of a society. Language has also experienced changes with the emergence of pop culture phenomena (popular culture). These changes reflect societal trends and changes. By analyzing the interrelationships of language, culture and society, this research provides insight into the complex dynamics of identity formation and their implications for social cohesion.